Supplement of liquid nutrient for fatigue recovery after tennis - Zhao, Chao (Progress in Nutrition, 2019)
Objective: The objective of this study is to study the relief effect of liquid nutrient containing whey protein on fatigue of tennis players caused by plenty of exercises. Methods: Twenty research subjects were randomly divided into a pure water group (n = 10) and a whey protein group (n = 10), and they took tennis training after taking same dose of pure water and whey protein. The weight and fat-free weight of the players were measured before and after experiment. The red blood cells (RBC), hemoglobin (HB), blood lactic acid (BLA) and creatine kinase (CK) were detected through blood sampling. Results: After experiment, the fat-free weight of the whey protein group was significantly higher than that of the pure water group (P < 0.05), the RBC and HB of the whey protein group were higher (P < 0.05), and the BLA and CK of the whey protein group were lower (P < 0.05). Conclusion: The supplement of whey protein liquid nutrient is beneficial to promoting the generation of RBC and HB, reducing lactic acid accumulation, and inhibiting the increase of serum creatine phosphokinase, which is helpful to the recovery of exercise induced fatigue.